From Villain to Class Hero - Czapo, Marg (Canadian Journal of Counselling and Psychotherapy, 2012)
Disturbed behaviors are often maintained by variables in the educational environment. An effective classroom rehabilitation program involves the alteration of the variables which maintain inappropriate behaviors. An intervention plan was designed for a ten-year-old emotionally disturbed boy which included positive feedback for academic achievement and positive social emotional feedback from the peers. The environmental variables were redesigned to promote success instead of failure and to gain acceptance instead of rejection. The intervention consisted of rewarding appropriate academic and social behaviors. Each time the subject earned a point for himself he earned a point for the class towards a desirable class event. The results indicate that the alteration of feedback conditions resulted in alteration of behavior in the subject, the teacher, and the peers. In the changed classroom environment the frequency of maladaptive behaviors decreased.